Optimal Taxation with Private Government Information - Sleet, Christopher (Review of Economic Studies, 2004)
The Ramsey model of fiscal policy implies that taxes should be smooth in the sense of having small variances. In contrast, empirical labour tax processes are smooth in the sense of being random walks; they provide prima facie evidence for incomplete government insurance. This paper considers whether private government information might lie behind such incomplete insurance. It shows that optimal incentive compatible policies exhibit limited use of state contingent debt and greater persistence in taxes and debt, and it argues that they are better approximations to empirical fiscal policies than those implied by the Ramsey model. The paper also establishes that optimal incentive compatible allocations converge to allocations such that the government's incentive compatibility constraint no longer binds. Generally, these limiting allocations are ones in which the government is maximally indebted. Their credibility and the interaction of incentive compatibility and credibility is briefly discussed.